The first record of \(Kudoa yasunagai\) (Hsieh & Chen, 1984) (Myxosporea: Multivalvulida) parasitizing the brain of barhead spinefoot \(Siganus virgatus\) (Valenciennes) from Vietnam - Nguyen Ngoc, Chinh; Shirakashi, Sho (Academia Journal of Biology, 2024)
A brain-infecting myxozoan, Kudoa yasunagai (Hsieh & Chen, 1984), was identified using both morphological and molecular methods in a marine fish from Van Phong Bay, Khanh Hoa province, Vietnam. Cysts containing spores were observed in the brain of one out of 10 Siganus virgatus (Valenciennes) individuals (10%). The myxospores were radially symmetrical, containing a majority of 7 equal shell valves and polar capsules. The spores measured 6.6 ± 0.1 (6.4‒6.7) µm in length, 7.6 ± 0.5 (7.0‒8.4) µm in width, and 7.0 ± 0.4 (6.5‒7.7) µm in thickness. Polar capsules measured 2.8 ± 0.2 (2.6‒3.0) µm in length and 1.4 ± 0.1 (1.2‒1.5) µm in width, containing a filament inside. The SSU rDNA sequence from the Vietnamese specimen showed > 99.94 % identity with K. yasunagai from Japan and Australia. This report marks a new geographical and host record for K. yasunagai.